OBSERVATIONS ON THE PRIMARY MARINE PRODUCTIVITY OF NORTHWESTERN INDONESIAN WATERS - Dotty, Maxwell S.; Soeriaatmadja, Raden Engkoes; Soegiarto, Aprilany (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1963)
During the fall months of 1957, a scientific cruise was completed in some of the more northwestern fishery areas of Western Indonesia (Fig. 1) on the Indonesian research vessel